Śrīkaṇṭhatīrtha : Tī. Naṃ.Śrī. smārakagrantha - Śrīkaṇṭhayya, Tī. Naṃ., 1906-1966; Murthy, M. Chidananda; Nāgabhūṣaṇa, Tī. Śrī (Tī. Naṃ.Śrī. Saṃsāravarga, 1976)
Festschrift honoring Ti. Naṃ. Śrīkaṇṭhayya, 1906-1966, Kannada litterateur; comprises articles on his life, literary career, and Kannada literature.